2-{[(2-Hydroxy-3,5-dimethylbenzyl)(methyl)amino]methyl}-4,6-dimethylphenol - Veranitisagul, Chatchai (International Union of Crystallography, 2012)
In the title compound, C(19)H(25)NO(2), the dihedral angle between the benzene rings is 53.15 (8)°. One of the –OH groups forms an intramolecular O—H⋯N link, generating an S(6) ring. The other –OH group forms an intermolecular O—H⋯N hydrogen bond in the crystal, generating centrosymmetric R (2) (2)(20) loops.